Crisis response information networks - PAN, Shan L. (Institutional Knowledge at Singapore Management University, 2012)
In the past two decades, organizational scholars have focused significant attention on how organizations manage crises. While most of these studies concentrate on crisis prevention, there is a growing emphasis on crisis response. Because information that is critical to crisis response may become outdated as crisis conditions change, crisis response research recognizes that the management of information flows and networks is critical to crisis response. Yet despite its importance, little is known about the various types of crisis information networks and the role of IT in enabling these information networks. Employing concepts from information flow and social network theories, this paper contributes to crisis management research by developing four crisis response information network prototypes. These networks are based on two main dimensions: (1) information flow intensity and (2) network density. We describe how considerations of these two dimensions with supporting case evidence yield four prototypical crisis information response networks: Information Star, Information Pyramid, Information Forest, and Information Black-out. In addition, we examine the role of IT within each information network structure. We conclude with guidelines for managers to deploy appropriate information networks during crisis response and with suggestions for future research related to IT and crisis management.